The efficacy and safety of prostatic urethral lift as a minimally invasive therapeutic modality to treat lower urinary tract symptoms while maintaining sexual function in patients with benign prostatic hyperplasia: a systematic review and meta-analysis of randomized controlled trials - Syah Mirsya Warli; Muhammad Fahmi Ikram; Raja Gerald Sarumpaet; Zaimah Zulkarnaini Tala; Ignatius Ivan Putrantyo (Archivio Italiano di Urologia e Andrologia, 2024)
Background: Benign Prostatic Hyperplasia (BPH) is prevalent among elderly men, necessitating focused attention. The Prostatic Urethral Lift (PUL) procedure, a minimally invasive intervention, has emerged as a promising option for BPH management. It has shown remarkable results in ameliorating Lower Urinary Tract Symptoms (LUTS), enhancing quality of life, and preserving sexual function. This study aims to evaluate the effectiveness and safety of PUL in BPH patients. Methods: Key databases (MEDLINE, Cochrane CENTRAL, ScienceDirect, EBSCO, Google Scholar) were systematically searched using pertinent terms related to PUL and BPH. Following the PRISMA checklist, we considered only Randomized Controlled Trials studies (RCTs) from 2013 to 2023. The assessment focused on LUTS, Quality of Life, sexual function, and Adverse Events, within three months. Follow-up post-treatment mean values compared with controls (Sham) and the improvement from baseline to post-treatment follow-up duration were considered. Statistical analysis and risk of bias evaluation were conducted using Review Manager 5.4.1, presenting results as difference of mean values (MD) and Risk Ratios (RR). Results: A meta-analysis with a Random Effects Model of 7 RCTs involving 378 confirmed BPH patients demonstrated significant improvements in the PUL arm including International Prostate Symptom Score (IPSS) (MD 5.51, p < 0.0001), maximum urinary flow rate (Qmax) (MD 2.13, p = 0.0001), BPH Impact Index (BPHII) (MD 2.14, p = 0.0001), and IPSS-QoL (MD 1.50, p < 0.0001), without significant increase of Adverse Events (RR 1.51; p = 0.50). Positive outcomes were observed in sexual function variables and post-void residual measurements when post-treatment values were compared to baseline. Conclusions: PUL holds advantages over control interventions, providing encouraging prospects for BPH management. This study underscores the need for further exploration of PUL's efficacy and safety in BPH patients.